Methods for determining periodontal biotype: A review of the literature. - Tello, Damián (2021)
To carry out various dental interventions, a correct evaluation of the periodontal biotype is necessary, for which it is necessary to know the different methods of evaluating the periodontal biotype. 8 methods are known to determine the periodontal biotype, among which we have: visual, probe transparency, transgingival evaluation, ultrasound, computed tomography, modified calibrator, photographic analysis and cone beam computed tomography. There are several widely used methods to determine the periodontal biotype, however, among the methods analyzed, cone beam computed tomography has high precision and minimal deviation when compared with conventional methods such as probe transparency, transgingival evaluation or visual method for accurately determine the periodontal biotype.